Investigation of structural elastic electronic optical and thermoelectric properties of LiInS₂ and LiInTe₂ for optoelectronic and energy conversion - M. Fatmi; K. Bouferrache; M. A. Ghebouli; B. Ghebouli; S. Alomairy; Faisal Katib Alanazi (Scientific Reports)
Abstract In this research, the structural, electronic, optical, and thermoelectric properties of LiInX₂ (X = S, Te) compounds were investigated using first-principles calculations based on Density Functional Theory (DFT). The Full-Potential Linearized Augmented Plane Wave (FP-LAPW) method implemented in the Wien2k package was employed, with the Generalized Gradient Approximation (GGA) and Tran-Blaha modified Becke-Johnson (mBJ-GGA) approximation applied to study the electronic properties. The results revealed that LiInS₂ crystallizes in an orthorhombic system with space group Pna21, while LiInTe₂ crystallizes in a tetragonal system with space group I-42d. The lattice constants and elastic parameters were calculated, showing good agreement with available experimental values. The elastic properties, including elastic constants, moduli, and mechanical stability criteria, were also evaluated to provide insight into the structural robustness and potential mechanical performance of the compounds. Electronic band structure calculations revealed that both compounds possess direct band gaps, with values of 3.61 eV for LiInS₂ and 2.33 eV for LiInTe₂ using the mBJ-GGA approximation, which are close to experimental measurements. Phonon dispersion studies were conducted to verify the dynamic stability of both compounds. Our findings demonstrate that LiInX₂ (X = S, Te) compounds possess suitable electronic band structures, strong optical absorption in the visible and UV ranges, and favorable thermoelectric characteristics. These results highlight their potential as promising materials for both optoelectronic devices and thermoelectric energy conversion technologies.